2018
DOI: 10.1177/1071100718800295
|View full text |Cite
|
Sign up to set email alerts
|

Combined Subtalar and Naviculocuneiform Fusion for Treating Adult Acquired Flatfoot Deformity With Medial Arch Collapse at the Level of the Naviculocuneiform Joint

Abstract: Background: A challenge in treating acquired flatfoot deformities is the collapse of the medial arch at the level of the naviculocuneiform (NC) joint. Triple fusions, being a treatment option, may lead to problems such as increased foot stiffness. We thus established a method that combines subtalar (ST) fusion with NC fusion while preserving the Chopart joint. We analyzed the radiographic correction, fusion rate, and patient satisfaction with this procedure. Methods: 34 feet in 31 patients (female, 23; male, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Some authors have advocated for NC fusion in cases of substantial midfoot sag, but the indications for this procedure are not well defined. 24,29 Steiner et al examined the role of combined ST and NC fusion in restoring medial arch collapse in severe flatfoot deformity. The authors demonstrated in their cohort of patients a significant correction in Meary angle, talocalcaneal angle, TN coverage, and HMA, concluding that collapse at the medial arch can be restored with these procedures with good clinical and radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have advocated for NC fusion in cases of substantial midfoot sag, but the indications for this procedure are not well defined. 24,29 Steiner et al examined the role of combined ST and NC fusion in restoring medial arch collapse in severe flatfoot deformity. The authors demonstrated in their cohort of patients a significant correction in Meary angle, talocalcaneal angle, TN coverage, and HMA, concluding that collapse at the medial arch can be restored with these procedures with good clinical and radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated in their cohort of patients a significant correction in Meary angle, talocalcaneal angle, TN coverage, and HMA, concluding that collapse at the medial arch can be restored with these procedures with good clinical and radiographic outcomes. 29 However, the necessity of correcting deformity at the NC joint has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Other exclusion criteria were additional bony procedures on the hindfoot [i.e. subtalar arthrodesis (n = 37) or medial sliding calcaneus osteotomy (n = 9)] or the medial column (Cotton osteotomy, arthrodesis of the 1st tarsometatarsal joint [15,16] or the navicular-cuneiform joint [17,18] (n, in total = 18)), lack of preoperative MRI or CT of the hindfoot (n = 10), and lack of pre-and postoperative complete conventional radiographs (weight-bearing lateral and dorsoplantar views) (n = 2) with a minimum follow-up of 3 months.…”
Section: Study Populationmentioning
confidence: 99%
“…However, the concept of using an NC fusion instead TN fusion was reported to be successful in correcting and stabilizing the forefoot. 34,35 With the hypothesis that attenuation of the medial supporting structures of the foot results in the progression of the PCFD, Miller 28 was the first to propose correction of the medial alignment of the foot by fusion of the medial column, specifically, a fusion of the NC and first TMT joints. In addition to the medial column fusion, he performed an advancement of the PTT complex as an osteoperiosteal flap.…”
Section: Rationalementioning
confidence: 99%
“…2,13 Even though prior literature has reported important nonunion rates of NC joint fusions, 20,28,34 using this surgical technique, union of both joints was found in 32 of 34 cases; a nonunion occurred in only 1 case at the ST joint and in 1 case at the NC fusion site, but the patient remained asymptomatic. 35 The low nonunion rate could potentially be explained by a protective effect of the ST fusion stability to the fusion site at the NC joint, possibly decreasing the mechanical overload in this joint, even with early weightbearing as tolerated being allowed immediately postoperatively. In 15 cases (44%), an additional medial sliding osteotomy of the calcaneus was performed to achieve the required correction of hindfoot alignment, and in 5 cases (14.7%), an FDL tendon transfer was done.…”
Section: Rationalementioning
confidence: 99%